Allergic contact dermatitis to methylisothiazolinone: Exposure from baby wipes causing hand dermatitis. (29th May 2013) - Boyapati, Ann; Tam, Mei; Tate, Bruce; Lee, Adriene; Palmer, Amanda; Nixon, Rosemary
Abstract: Background/Objectives: Methylchloroisothiazolinone/methylisothiazolinone (MCI/MI) is a preservative used in both cosmetic and industrial settings. In Europe it is allowed to be used in rinse‐off cosmetics only because of its propensity to cause allergic contact dermatitis (ACD). No such legislation exists in Australia. In recent years MI without MCI has been used. In August 2010 the first cases of MI causing non‐occupational ACD were reported in Europe. The objective here was to present a case series of ACD to MI occurring in the Australian setting. Methods: : We retrospectively reviewed positive reactions to MI and MCI/MI from the Skin and Cancer Foundation patch test clinical database. MI was added to our baseline test series in January 2011. Results: : In total 653 patients were tested for MI and there were 43 reactions, of which 23 were relevant, based on a history of exposure to MI. Seven were parents of young children with hand dermatitis caused by ACD to MI contained in baby wipes. The remaining patients reacted to MI in shampoos, conditioners, deodorants, moisturisers, a skin cleanser and a facial wipe. Three patients had ACD to MI associated with occupational exposure to hand cleansers. Conclusions: These data demonstrate for the first time that MI is an emerging, important allergen in both cosmetic and occupational settings in Australia. An important source of exposure was baby wipes, which was predominantly associated with hand dermatitis in parents. We believe that it is important to test for MI, not just MCI/MI, in the baseline series.